2019
DOI: 10.3390/su11164461
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Opinion Leaders’ Characteristics on Online Group Knowledge-Sharing Engagement from In-Group and Out-Group Perspectives: Evidence from a Chinese Online Knowledge-Sharing Community

Abstract: Opinion leaders often play key roles in online knowledge-sharing communities, which has intrigued a lot of researchers and practitioners worldwide. However, it is not clear how various characteristics of opinion leaders may affect different online groups’ knowledge-sharing engagement. This paper aims to answer this question by building upon social capital theory to examine the differential influences of opinion leaders’ characteristics (interactivity, authority, and activity) on online groups. In-groups and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…In OBCs, concrete plans should be adopted to promote an affiliative and self-enhancing humorous atmosphere, with some well-organized funny activities taking place regularly, such as contests to create short comedic videos. Due to the importance of key opinion leaders during information diffusion, managers need to fuel the participatory desires of these influencers, characterized by interactivity, authority and activity (Liu et al , 2019), and implement incentives for their high-quality humor content generation. Furthermore, owing to an emotional contagion process among members, light-hearted and funny topics, such as sharing humorous stories, should be scheduled to encourage intermember emotional responses.…”
Section: Discussionmentioning
confidence: 99%
“…In OBCs, concrete plans should be adopted to promote an affiliative and self-enhancing humorous atmosphere, with some well-organized funny activities taking place regularly, such as contests to create short comedic videos. Due to the importance of key opinion leaders during information diffusion, managers need to fuel the participatory desires of these influencers, characterized by interactivity, authority and activity (Liu et al , 2019), and implement incentives for their high-quality humor content generation. Furthermore, owing to an emotional contagion process among members, light-hearted and funny topics, such as sharing humorous stories, should be scheduled to encourage intermember emotional responses.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) found that the organizational innovation atmosphere can promote the knowledge-sharing behavior of employees. Liu et al. (2019) found that the activity of virtual community affects knowledge-sharing.…”
Section: Theoretical Basismentioning
confidence: 99%
“…The social capital theory comes with a provision to generalise insights into the process influencing the continuation of interpersonal relationships and is often applied to analyse user attitude and intention, especially in the area of sharing information to influence other people’s intentions (Chiu et al , 2006). The crux of the theory rests on the need to address the individual members’ resources (Liu et al , 2019). Additionally, opinion leaders have expertise and resources to guide the international students in choosing a sustainable university that suits their demands as customers.…”
Section: The Influence Of Opinion Leaders On Students’ Intention To S...mentioning
confidence: 99%